2022
DOI: 10.1002/hep.32702
|View full text |Cite
|
Sign up to set email alerts
|

The NADPH oxidase NOX4 regulates redox and metabolic homeostasis preventing HCC progression

Abstract: Background and Aims:The NADPH oxidase NOX4 plays a tumorsuppressor function in HCC. Silencing NOX4 confers higher proliferative and migratory capacity to HCC cells and increases their in vivo tumorigenic potential in xenografts in mice. NOX4 gene deletions are frequent in HCC, correlating with higher tumor grade and worse recurrence-free and overall

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…On the other hand, NOX4 has been reported to act as a tumour suppressor or oncogene depending on the tumour type. In HCC, NOX4 has been described to prevent cancer progression (Crosas-Molist et al , 2014, Penuelas-Haro et al , 2022). For these reasons we analyzed Nox4 expression, and observed reduced Nox4 mRNA levels in all three cell lines upon glutamine deprivation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, NOX4 has been reported to act as a tumour suppressor or oncogene depending on the tumour type. In HCC, NOX4 has been described to prevent cancer progression (Crosas-Molist et al , 2014, Penuelas-Haro et al , 2022). For these reasons we analyzed Nox4 expression, and observed reduced Nox4 mRNA levels in all three cell lines upon glutamine deprivation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A research group from Shanghai detected preoperative and postoperative circulating tumor cells (CTCs) of 193 patients and found the predictive value of CTCs for tumor recurrence in patients with HCC following LT 51 . Also, multiomics technologies such as mass cytometry, proteomics, transcriptomics, radiomics, and metabolomics, can be powerful tools to explore the mechanisms of tumor development and identify key molecule or cell cluster in cancer recurrence 52 55 .…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of redox homeostasis is closely linked to the development of HCC. Notably, studies have demonstrated that the deletion of NADPH oxidase NOX4 triggers the activation of the MYC pathway, resulting in a perturbation of redox homeostasis, perturbed oxidative metabolism, and ultimately facilitating the progression of HCC [92].…”
Section: Redox Metabolismmentioning
confidence: 99%